Prevalence of Mask Using Behavior During Covid-19 Pandemic - Titik Haryanti; Akhmad Azmiardi; Dewi Puspito Sari; Sumardiyono Sumardiyono (Jurnal Ilmu Kesehatan Masyarakat Berkala, 2021)
This research is an observational analytic study with a cross-sectional study design. This research was conducted in Sukoharjo Regency in November 2020. A total of 246 research subjects were obtained using simple random sampling. The dependent variable in this study was the use of masks. The independent variables in this study were age, education, knowledge, attitudes, and perceived threat. The data was obtained using an online questionnaire via google form. Biavariate analysis with Chi-Square. The results of this study obtained the prevalence of behavior using masks 226 people (91.87%). Factors that influence the behavior of using masks high knowledge (OR= 7.44; p<0.001), positive attitude (OR= 3.71; p= 0.005), and high threat perception. (OR= 2.68; p=0.031).